Animal fat replacement by vegetable oils in formulations of breads with flour mixes - Osuna, Mariana B. (2018)
The improvement of fatty acids (FA) profile of bread made with bovine fat (BF) and a mixture of flours completely replacing fat with canola oil (CO), or olive oil (OO) was evaluated. Technological and sensory characteristics and overall acceptability of the fortified breads were also studied. The results showed a decrease in saturated FA and a relative increase in monounsaturated and polyunsaturated FA compared to bread made with BF. Regarding CO, this caused the higher increase in n3 FA. This effect was maximized in bread made from the mixture of wheat flour (WF) + flaxseed flour (FF) + soybean flour (SF). OO caused a rise of n9 and n6 FA, mainly in bread made with WF + FF + wheat bran (WB). The breads with WF + FF + SF + CO and WF + FF + WB + OO presented higher specific volume, softer crumb and colour similar to those from base formulations. Furthermore, they had a very good sensory acceptance.